High-throughput imaging of ATG9A distribution as a diagnostic functional assay for adaptor protein complex 4-associated hereditary spastic paraplegia. Issue 4 (25th September 2021) - Ebrahimi-Fakhari, Darius; Alecu, Julian E; Brechmann, Barbara; Ziegler, Marvin; Eberhardt, Kathrin; Jumo, Hellen; D'Amore, Angelica; Habibzadeh, Parham; Faghihi, Mohammad Ali; De Bleecker, Jan L; Vuillaumier-Barrot, Sandrine; Auvin, Stéphane; et al.
Abstract: Adaptor protein complex 4-associated hereditary spastic paraplegia is caused by biallelic loss-of-function variants in AP4B1, AP4M1, AP4E1 or AP4S1, which constitute the four subunits of this obligate complex. While the diagnosis of adaptor protein complex 4-associated hereditary spastic paraplegia relies on molecular testing, the interpretation of novel missense variants remains challenging. Here, we address this diagnostic gap by using patient-derived fibroblasts to establish a functional assay that measures the subcellular localization of ATG9A, a transmembrane protein that is sorted by adaptor protein complex 4. Using automated high-throughput microscopy, we determine the ratio of the ATG9A fluorescence in the trans-Golgi-network versus cytoplasm and ascertain that this metric meets standards for screening assays (Z′-factor robust >0.3, strictly standardized mean difference >3). The 'ATG9A ratio' is increased in fibroblasts of 18 well-characterized adaptor protein complex 4-associated hereditary spastic paraplegia patients [mean: 1.54 ± 0.13 versus 1.21 ± 0.05 (standard deviation) in controls] and receiver-operating characteristic analysis demonstrates robust diagnostic power (area under the curve: 0.85, 95% confidence interval: 0.849–0.852). Using fibroblasts from two individuals with atypical clinical features and novel biallelic missense variants of unknown significance in AP4B1, we show that our assay can reliably detect adaptor protein complex 4 function. Our findings establish the 'ATG9A ratio' as a diagnostic marker of adaptor protein complex 4-associated hereditary spastic paraplegia. Abstract : Ebrahimi-Fakhari et al. establish the intracellular ATG9A distribution as a diagnostic marker for AP-4-associated hereditary spastic paraplegia using a novel high-throughput assay in patient-derived fibroblasts. This approach enables the functional validation of novel variants in AP4B1, AP4M1, AP4S1 and AP4E1 with robust diagnostic power and opens opportunities for biomarker discovery. Graphical Abstract: